The Mind of an Engineer - Ghosh, Purnendu; Raj, Baldev; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The Indian National Academy of Engineering (INAE) promotes the endeavour of the practitioners of engineering and technology and related sciences to solve the problems of national importance. The book is an initiative of the INAE and a reflection of the experiences of some of the Fellows of the INAE in the fields of science, technology and engineering. The book is about the reminiscences, eureka moments, inspirations, challenges and opportunities in the journey the professionals took toward self-realisation and the goals they achieved. The book contains 58 articles on diverse topics that truly reflects the way the meaningful mind of an engineer works. .
Chapter 1. The Mind of An Engineer -- Chapter 2. Directed and Systematic Approaches Towards Sustainability in the 21st Century -- Chapter 3. Treating Challenges as Opportunities -- Chapter 4. Mind to Chemical Markets: Engineering and Managing the Complex Journey -- Chapter 5. The Search for Meaningful Purpose: Reminiscences of an Indian Engineer -- Chapter 6. An Engineer or a Scientist - A Perpetual Dilemma -- Chapter 7. Is an Engineer's Mind Different? -- Chapter 8. Technology and the Global Community -- Chapter 9. The Anatomy of Change -- Chapter 10. India's Tryst with Destiny - Establishment of the Highest Level of Engineering and Technology -- Chapter 11. Glimpses from a Lifetime in Teaching and Research -- Chapter 12. My Four Decades in BARC -- Chapter 13. Think to do Something -- Chapter 14. The Milestones of My Professional Life -- Chapter 15. Reminiscing My Days at the Vikram Sarabhai Space Centre (VSSC), Trivandrum -- Chapter 16. Chasing a Dream -- Chapter 17. My Eureka Moment -- Chapter 18. My Reminiscences -- Chapter 19. From "Nowhere to Somewhere" -- Chapter 20. My Life in An Encouraging Educational and Professional Environment -- Chapter 21. The Journey from a Village as a Farmer's son to Fashion World as a Scientist in Leather -- Chapter 22. Forty Years of Academics and Administration: Experiences and Lessons -- Chapter 23. Creativity - A Personal Challenge -- Chapter 24. Life - A Journey of Learning -- Chapter 25. Some Views and Experience on the Mind of an Engineer -- Chapter 26. A Tribute to Some of my "Teachers" who Mattered the Most -- Chapter 27. A Journey of a Self-realization -- Chapter 28. A Sketch of My Life.-Chapter 29. A Humble Journey -- Chapter 30. My Experiences -- Chapter 31. My Experiences in Creating Indigenous Technology Enterprise in India -- Chapter 32. My Journey as a Materials Engineer -- Chapter 33. My Experiences at IIT Kanpur -- Chapter 34. Journey I enjoyed amidst Challenges -- Chapter 35. Reminisces from the Past -- Chapter 36. Engineering Challenges - A Personal Account -- Chapter 37. From Academia with Love -- Chapter 38. The House of Education -- Chapter 39. Need of Promotion of Innovation in Indian Engineering Institutes -- Chapter 40. From Physics to Engineering Physics -- Chapter 41. Physicist or Metallurgist -- Chapter 42. Commercialization of Indigenously Developed Technologies -- Chapter 43. Hydrodynamic Cavitation Technology: Industrial Applications -- Chapter 44. R&D - Another Oxymoron -- Chapter 45. Ten Levers of Smart Engineering -- Chapter 46. Life with Experiments -- Chapter 47. Playing with Fuzziness and Ambiguity in Patterns - Challenges and Achievements -- Chapter 48. A view of India through Kolam Patterns and their Grammatical Representation -- Chapter 49. A Logical Perspective of Formal Verification a Narrative on the Genesis and Evolution of the Formal Verification Group at IIT Kharagpur -- Chapter 50. Engineering and Innovation in Manufacturing and Production of Akash Missile System -- Chapter 51. The First Steps Towards Self-reliance in Solid Propellant Rockets -- Chapter 52. Challenges in Developing Indigenous Technology -- Chapter 53. The Challenge of Developing a High Speed Rotor Assembly - How It was Met -- Chapter 54. My Tryst with Indigenous Armour Development -- Chapter 55. Inertial Sensors and Navigation Systems -- Chapter 56. Perspectives on Technology Trends in Biopharmaceuticals Manufacture -- Chapter 57. The Hydro Power Development in India - Challenges and Way Forward -- Chapter 58. Integrated Coastal Zone Management of Chilka Lake. .
Keywords: Technology -- Sociological aspects; Engineering; Science -- Study and teaching; Science, Technology and Society; Technology and Engineering; Science Education